ENGLISH COCKNEY SLANG LANGUAGEIN THE BUILDING OF CHARACTERIZATION IN MOVIES - Fachmy Hendrawan, - (2005)
This study is investigating English Cockney Slang Language in the Building of Characterization in Movies (a case study on the movies entitled Trainspotting and Lock, Stock and Two Smoking Barrels). In this research, I use a descriptive method to analyze English Cockney Slang Language in the Building of Characterization in Movies. Since the formulated research questions call for an analysis in qualitative tradition, the descriptive method refers to the analysis employing the features of qualitative study. This study centers on answering the three research questions. First, how does English Cockney Slang Language build Characterization in Trainspotting and Lock, Stock and Two Smoking Barrels Movies? Second, in what scene is English Cockney Slang language mostly used? Third, what characterization mostly uses English Cockney Slang Language? The research employs the textual evidence analysis. The subjects of the analysis are the characters who use English Cockney Slang Language on the movies entitled Trainspotting and Lock, Stock and Two Smoking Barrels. This paper may have a valuable contribution to the students' who are concerned with modern literary criticism; especially those who are interested in movies in their research and this may enrich students' knowledge and their understanding on literary theories